Transitional dynamics of modern languages and applied language studies: at a crossroad / Ahmad Mazli Muhammad - Muhammad, Ahmad Mazli (Akademi Pengajian Bahasa, 2021)
The COVID-19 pandemic has brought education to a crossroad. The status quo of all levels and fields of education (including language education at the university level) that existed prior to that, was deliberately rocked to its foundation. Almost overnight, higher education experienced a tsunami that literally caught the education fraternity off guard. Questions were raised, problems were analysed, solutions were provided, and interventions were implemented. All these happened within a short duration. Many a time, history has proven that sudden changes may result in less desirable outcomes. This session looks objectively at the past with an understanding that the knowledge and experience of the past and the very recent past (prior to the pandemic) may lead to new research areas that can contribute to an effective ecosystem and culture of language education at higher education.